“PENGARUH STURKTUR KEPEMILIKAN TERHADAP NILAI PERUSAHAAN DENGAN CORPORATE SOCIAL RESPONSIBILITY SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN JASA KEUANGAN YANG TERDAFTAR DI BEI TAHUN 2013-2016” - Siska Nofita Ana Pertiwi, 14.05.51.0203; Hersugondo, Hersugondo (Students' Journal of Economic and Management, 2018)
The purpose of this research is to know the influence of Ownership Structure of Foreign Ownership (Forgn_Own), Institutional Ownership (Ints_Own), and Public Ownership (Public_Own) on Corporate Value with Corporate Social Responsibility (CSR) as intervening variable in registered financial services company in Indonesia Stock Exchange 2013-2016. The research population is a financial services company listed on the Indonesia Stock Exchange in the year 2013-2016 as many as 248 companies. While in the sampling by using purposive sampling method. With this method, there are 130 companies that meet the criteria. Data is obtained through Annual Report and Monthly. The results show that Corporate Social Responsibility (CSR) has a positive and significant impact on Corporate Value, foreign ownership (Forgn_Own), Institutional ownership (Ints_Own), and public ownership (Public_Own) have a positive and significant impact on Corporate Social Responsibility (CSR) in financial services companies listed on the Stock Exchange Year 2013-2016. Foreign ownership (Forgn_Own), Institutional Ownership (Ints_Own), and Public Ownership (Public_Own) have a positive and significant impact on Corporate Value of financial services companies listed on the Stock Exchange 2013-2016. And indirectly or through CSR, foreign ownership (Forgn_Own), institutional ownership (Ints_Own), and public ownership (Public_Own) also have a positive and Significant effect on Corporate Value on financial services companies listed on the Stock Exchange in 2013- 2016. However, in this study, Corporate Social Responsibility (CSR) does not act as a full interval or mediation variable but serves as a half-mediation variable.Keywords: Foreign Ownership (Forgn_Own), Institutional Ownership (Ints_Own), Public Ownership (Public_Own), Corporate Social Responsibility (CSR), Corporate Value